Matrix-induced autologous chondrocyte implantation in sheep: objective assessments including confocal arthroscopy - Jones, C. W.; Willers, C.; Keogh, A.; Smolinski, D.; Fick, D.; Yates, P. J.; Kirk, T. B.; Zheng, M. H. (Journal of orthopaedic research, 2008)
The assessment of cartilage repair has largely been limited to macroscopic observation, magnetic resonance imaging (MRI), or destructive biopsy. The aims of this study were to establish an ovine model of articular cartilage injury repair and to examine the efficacy of nondestructive techniques for assessing cartilage regeneration by matrix‐induced autologous chondrocyte implantation (MACI). The development of nondestructive assessment techniques facilitates the monitoring of repair treatments in both experimental animal models and human clinical subjects. Defects (Ø 6 mm) were created on the trochlea and medial femoral condyle of 21 sheep randomized into untreated controls or one of two treatment arms: MACI or collagen‐only membrane. Each group was divided into 8‐, 10‐, and 12‐week time points. Repair outcomes were examined using laser scanning confocal arthroscopy (LSCA), MRI, histology, macroscopic ICRS grading, and biomechanical compression analysis. Interobserver analysis of the randomized blinded scoring of LSCA images validated our scoring protocol. Pearson correlation analysis demonstrated the correlation between LSCA, MRI, and ICRS grading. Testing of overall treatment effect independent of time point revealed significant differences between MACI and control groups for all sites and assessment modalities (Asym Sig < 0.05), except condyle histology. Biomechanical analysis suggests that while MACI tissue may resemble native tissue histologically in the early stages of remodeling, the biomechanical properties remain inferior at least in the short term. This study demonstrates the potential of a multisite sheep model of articular cartilage defect repair and its assessment via nondestructive methods. © 2007 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 26:292–303, 2008